2003
DOI: 10.1176/appi.ajp.160.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Correlates of Suicide Attempts Over 5 Years in 1,237 Alcohol-Dependent Men and Women

Abstract: A 5-year prospective evaluation of attributes associated with suicide attempts among alcohol-dependent persons identified factors that contributed to a small but significant proportion of the variance for future suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
2
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 42 publications
9
75
2
18
Order By: Relevance
“…It also is evident that alcohol abuse is strongly associated with mental disorders and suicidal behaviors (Gomberg, 1989;Kolves, Varnik, Tooding, & Wasserman, 2006;Preuss et al, 2003;Wilcox, Conner, & Caine, 2004). In this study, one third of the participants reported alcohol intoxication (got drunk at least once a month in the past 6 months), and these women were twice as likely to report suicidal ideation as their counterparts who did not abuse alcohol.…”
Section: Discussionmentioning
confidence: 59%
“…It also is evident that alcohol abuse is strongly associated with mental disorders and suicidal behaviors (Gomberg, 1989;Kolves, Varnik, Tooding, & Wasserman, 2006;Preuss et al, 2003;Wilcox, Conner, & Caine, 2004). In this study, one third of the participants reported alcohol intoxication (got drunk at least once a month in the past 6 months), and these women were twice as likely to report suicidal ideation as their counterparts who did not abuse alcohol.…”
Section: Discussionmentioning
confidence: 59%
“…Studies from Western countries have demonstrated that alcohol and drug dependence increases the risk for suicidal attempts [38,39,40,41,42]. However, Akvardar et al [43] reported that dependence on illegal drugs in Turkey is rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a 5 year follow-up of alcoholics, clinical risk factors accounted for less than half of the variance for suicidal behavior, whereas genetic-epidemiologic studies indicate that up to half of the variance for attempting suicide is owing to genetic factors (Preuss et al, 2003;Statham et al, 1998;Glowinski et al, 2001;Fu et al, 2002). As low central serotonin function is implicated in suicidal behavior, we examine here the possible role of the serotonin transporter gene in suicidal behavior among substance dependent patients (Asberg, 1997).…”
Section: Introductionmentioning
confidence: 99%